Use of thyroid hormones in euthyroid patients with unexplained fatigue: analyses of aggregate data from European national surveys of professional endocrine society members - Bednarczuk, Tomasz; Sugier, Aleksandra; Attanasio, Roberto; Nagy, Endre V.; Negro, Roberto; Papini, Enrico; Žarković, Miloš; Akarsu, Ersin; Alevizaki, Maria; Ayvaz, Göksun; Nedeljković Beleslin, Biljana; Berta, Eszter; et al. (Frontiers in Endocrinology, 2025)
BackgroundManaging patients with fatigue is a clinical challenge. Because fatigue is often reported in hypothyroidism, thyroid hormone (TH) therapy may sometimes be incorrectly considered for biochemically euthyroid individuals. This study aimed to evaluate the prevalence and determinants of this practice in different European countries.MethodsWe analyzed aggregate data from the THESIS (Treatment of Hypothyroidism in Europe by Specialists: an International Survey) online survey. We analyzed responses from 5,695 members of 28 national endocrine/thyroid societies’ specialists to the statement: “Thyroid hormones may be indicated in biochemically euthyroid patients with unexplained fatigue”.ResultsOverall, 7.5% (426/5695) of respondents indicated that TH therapy might be considered for euthyroid patients with unexplained fatigue. The proportion of positive responses varied widely across different countries (between 1.1% in Switzerland and 29.3% in Serbia; p=2 ×10-16) and regions (between 4.7% in Western Europe and 8.7% in Western Asia or 8.8% in Eastern Europe; p=0.004). TH were more frequently prescribed for unexplained fatigue by male respondents (Odds Ratio, OR 1.45, 95% CI 1.18-1.78) and physicians practicing in private practice (OR 1.27, 95% CI 1.02-1.58), and less frequently by endocrinologists (OR 0.62, 95% CI 0.46-0.83).ConclusionA small, yet not negligible percentage of European thyroid-focused physicians consider using TH for euthyroid patients with unexplained fatigue, with significant variations based on geographic, demographic, and practice-related factors. Using levothyroxine and/or liothyronine in such cases lacks evidence and may partially contribute to the concerning overuse of TH therapy.